Terror, education and America: a case study of a local Tea Party group in North Carolina - Kelly, Kristin B. (Kansas State University, 2014)
Street and DiMaggio (2011) argue that the national Tea Party movement is an extension of the Republican Party in the United States, claiming that it’s an “ugly, authoritarian, and fake-populist pseudo movement directed from above and early on by and for elite Republican and business interests” (p.9). On the other hand, Skocpol and Williams (2012) argue that “the Tea Party is neither a top-down creation nor a bottom-up explosion” (p.12). I argue that the North Carolina movement, at the local level, represents a group of grassroots activists who were first mobilized on December 2nd, 2005, according to the “Triangle Conservatives Unite!” website. Because of the South’s history with race relations and Ku Klux Klan violence in North Carolina around the issue of public education, for the purposes of this study I want to pose the following questions: How is Tea Party “craziness” functional for the local 9/12 project group, “Triangle Conservatives Unite!”? How is symbolic racism used as a framing device by the Tea Party, as a social movement, around public education in North Carolina? In order to capture Tea Party member and civil society attitudes toward the Wake County Board of Education decision to scrap the old, nationally-recognized socioeconomic diversity policy in favor of one that much resembled the 1960s neighborhood/community schools policy, I use a case study approach to look at how the Tea Party Social Movement deals with race, with regard to the Wake County School Board decision to go back to neighborhood/community schools. When analyzing popular news sources, I draw on Bonilla-Silva’s (2014) theory of Color-Blind Racism. I also draw on Tilly’s (1978) Resource Mobilization Theory to explain how the Tea Party Movement came to power in North Carolina, affecting the Wake County School Board Decision to go back to neighborhood schools. Major findings suggest that sometime after 2005, the group began to adopt the goals and mission statement of the national 9/12 project group, led by conservative commentator Glenn Beck. I also find mixed support for Bonilla-Silva’s (2014) theory of Color-Blind Racism as well as support for Tilly’s (1978) Resource Mobilization Theory in my study.
Keywords: Social movements; Political sociology; Race; Education; Sociology (0626)